Priority policy and actions of local government to promote climate-resilient and inclusive water, sanitation and hygiene (WASH) in Sarlahi and Dailekh districts in Nepal - KC, Sumitra; Khadka, Manohara; Nepal, Santosh; Koirala, Sanju; Aryal, Mamata (International Water Management Institute, 2024)
This study identifies critical gaps in water, sanitation and hygiene (WASH) policies and practices from a gender equality, disability and social inclusion (GEDSI) and climate change perspective and recommends actions for local governments to promote inclusive and resilient WASH services. The major institutional and policy challenges in the WASH sector in local governments in Dailekh and Sarlahi districts include a lack of local policies, a lack of coherence with federal laws and limited financial and technical capacity. Existing plans, policies and practices are less focused on the meaningful decision-making roles and specific needs of women, persons with disabilities and marginalized communities. To address these gaps, local governments should emphasize the formation of local plans and policies that meet community needs and align with national goals; enhance the capacity of user committees, wards and local government officials; strengthen monitoring mechanisms beyond infrastructure; engage with the private sector; and allocate a dedicated budget for climate-resilient and inclusive WASH.